Progress of in situ U-Th/He Isotopic Dating Technique and Its Application to Low Temperature Deposits - FU Shan-ling; ZHAO Cheng-hai (Yankuang ceshi, 2017)
The traditional single-grain U-Th/He isotopic dating method a uses time-consuming acid dissolution, correction for α-ejection and more requirements on target minerals (euhedral, transparent, no cracks or inclusions). in situ U-Th/He isotopic dating is a newly developed dating technique, which uses extracted 4He from target mineral by laser ablation system and analyzes the 4He and U, Th and other parent isotopes via the Noble Gas Mass Spectrum (Alphachron) coupled with laser system and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The U-Th/He age of the deposits can be acquired by an age calculation formula using the analytical results of 4He, U, and Th isotopes. The principles, analytical processes, and minerals suitable for dating, technique difficulty and application prospect in low-temperature mineral deposits, are presented in this paper. In situ U-Th/He dating technique solved two key problems compared to traditional single-grain method: (1) Correction of α-ejection is unnecessary, improving the reliability and accuracy of dating results, and (2) Overcoming the bias from heterogeneous distribution of parent isotopes (U, Th), enlarging the range of U-Th/He isotopic dating. Although the in situ U-Th/He isotopic dating technique still needs to address issues such as collateral heating, precise measurement of pit volume and standard materials, it has shown itself to be a promising prospect for silicates, phosphates and Fe-Ti oxides. With the improvement of the in situ U-Th/He isotopic dating technique, particularly the U-Th/He isotopic dating of hydrothermal sulfides, this technique will provide a better way to date low-temperature mineralization.